2020
DOI: 10.1177/1747493020932806
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in intracranial and extracranial atherosclerosis in patients with acute ischemic stroke

Abstract: Background and aim To investigate sex differences with respect to presence and location of atherosclerosis in acute ischemic stroke patients. Methods Participants with acute ischemic stroke were included from the Dutch acute stroke trial, a large prospective multicenter cohort study performed between May 2009 and August 2013. All patients received computed tomography/computed tomography-angiography within 9 h of stroke onset. We assessed presence of atherosclerosis in the intra- and extracranial internal carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…However, the coeffect of rs3130685-rs2222896-drinking increased CAD risk, here, the mutation of genes was the dominant factor for increasing risk of CAD. Smoking is an independent risk factor for accelerating atherosclerosis ( Taskinen and Borén, 2015 ; Voigt et al, 2020 ). However, in this study, it showed that minimal smoking independently reduced the risk of IS, and the synergy of minimal smoking with haplotype H1 significantly reduced the risk of IS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the coeffect of rs3130685-rs2222896-drinking increased CAD risk, here, the mutation of genes was the dominant factor for increasing risk of CAD. Smoking is an independent risk factor for accelerating atherosclerosis ( Taskinen and Borén, 2015 ; Voigt et al, 2020 ). However, in this study, it showed that minimal smoking independently reduced the risk of IS, and the synergy of minimal smoking with haplotype H1 significantly reduced the risk of IS.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these studies demonstrate that following carotid artery atherosclerosis, the expression of particular X-linked microRNAs (i.e., miR-188, miR-362, miR-503, miR-532, miR-542) is decreased and promotes VSMC proliferation. Although gene expression results in these studies were not stratified for women and men, these findings could provide a novel molecular mechanism for sex-specific atherosclerotic phenotypes given that extracranial atherosclerosis is less often present in women compared to men [ 74 ].…”
Section: Stroke Promoting Mechanismsmentioning
confidence: 99%
“…A recent study had reported that the association between the increased hypertension severity and the onset of ischemic stroke was almost twice as strong in women as in men ( Madsen et al, 2019 ). In addition, Voigt et al reported that the total and proximal plaque burdens were significantly higher for hypertensive male patients with acute ischemic stroke than for their female counterparts ( Voigt et al, 2021 ). Zhong et al reported that elevated plasma tHcy level predicted the poor prognosis of acute ischemic stroke for women, but not for men ( Zhong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Voigt et al reported that the total and proximal plaque burdens were significantly higher for hypertensive male patients with acute ischemic stroke than for their female counterparts (Voigt et al, 2021). Zhong et al reported that elevated plasma tHcy level predicted the poor prognosis of acute ischemic stroke for women, but not for men (Zhong et al, 2017).…”
Section: Dependent Variablesmentioning
confidence: 99%